Synthesis, Spectroscopic Characterization, and Biological Activities of Metal Complexes of 4-((4-Chlorophenyl)diazenyl)-2-((p-tolylimino)methyl)phenol - C. Anitha; C. D. Sheela; P. Tharmaraj; V. V. Hema (Journal of Chemistry)
Azo Schiff base complexes of VO(II), Mn(II), Co(II), Ni(II), Cu(II), and Zn(II) have been synthesized from 4-((4-chlorophenyl)diazenyl)-2-((p-tolylimino)methyl)phenol (CDTMP). The nature of bonding and the structural features of the complexes have been deduced from elemental analysis, molar conductance, magnetic susceptibility measurements, IR, UV-Vis, 1H-NMR, EPR, mass, SEM, and fluorescence spectral studies. Spectroscopic and other analytical studies reveal square-planar geometry for copper, square-pyramidal geometry for oxovanadium, and octahedral geometry for other complexes. The EPR spectra of copper(II) complex in DMSO at 300 K and 77 K were recorded, and its salient features are reported. Antimicrobial studies against several microorganisms indicate that the complexes are more potent bactericides and fungicides than the ligand. The electrochemical behavior of the copper(II) complex was studied by cyclic voltammetry. All the synthesized compounds can serve as potential photoactive materials as indicated from their characteristic fluorescence properties. The second harmonic conversion efficiency of the synthesized azo Schiff base was found to be higher than that of urea and KDP (potassium dihydrogen phosphate). SEM image of copper(II) complex implies the crystalline state and surface morphology of the complex.